A split-step shortens the time to perform a choice reaction step-and-reach movement in a simulated tennis task - Uzu, R.; Shinya, M.; Oda, S. (Journal of Sports Sciences, 2009)
In tennis, a "split-step" is a small vertical jump or hop that is commonly used as a preparatory motion for a lateral step when receiving the ball. The purposes of the present study were (1) to determine whether a split-step increases the velocity of the subsequent lateral step, and (2) to investigate when the landing should occur in order to obtain the maximum benefit from a split-step. Ten male collegiate tennis players performed a choice reaction step-and-reach task with and without a split-step. The participants could reach the target earlier by taking a split-step (split: 764 ± 106 ms, no-split: 868 ± 63, P < 0.001). A risk-benefit relationship of a split-step depended on the timing of the landing. If the interval between the activation of the direction signal and the landing was shorter than mean minus standard deviation of the participant's response time, participants sometimes achieved very quick step to the target but could not reach the target in 7.8% of the trials. On the contrary, if the interval between the activation of the direction signal and the landing was within the mean plus-minus standard deviation of the participant's response time, participants achieved quick and reliable (percentage of error: 0.8%) step.